Inflammatory and Antioxidant Pattern Unbalance in "Clopidogrel-Resistant" Patients during Acute Coronary Syndrome. (19th March 2015) - Caruso, Raffaele; Rocchiccioli, Silvia; Gori, Anna Maria; Cecchettini, Antonella; Giusti, Betti; Parodi, Guido; Cozzi, Lorena; Marcucci, Rossella; Parolini, Marina; Romagnuolo, Ilaria; Citti, Lorenzo; Abbate, Rosanna; et al.
Abstract : Background . In acute coronary syndrome (ACS), inflammation and redox response are associated with increased residual platelet reactivity (RPR) on clopidogrel therapy. We investigated whether clopidogrel interaction affects platelet function and modulates factors related to inflammation and oxidation in ACS patients differently responding to clopidogrel. Material and Methods . Platelet aggregation was measured in 29 ACS patients on dual (aspirin/clopidogrel) antiplatelet therapy. Nonresponders (NR) were defined as RPR ≥70% by ADP. Several inflammatory and redox parameters were assayed and platelet proteome was determined. Results . Eight (28%) out of 29 ACS patients resulted NR to clopidogrel. At 24 hours, the levels of Th2-type cytokines IL-4, IFN γ, and MCP-1 were higher in NR, while blood GSH (r-GSHbl ) levels were lower in NR than responders (R). Proteomic analysis evidenced an upregulated level of platelet adhesion molecule, CD226, and a downregulation of the antioxidant peroxiredoxin-4. In R patients the proinflammatory cytokine IL-6 decreased, while the anti-inflammatory cytokine IL-1Ra increased. Conclusions . In patients with high RPR on clopidogrel therapy, an unbalance of inflammatory factors, platelet adhesion molecules, and circulatory and platelet antioxidant molecules was observed during the acute phase. Proinflammatory milieu persists in nonresponders for a long time after the acute event while antioxidant blood factors tend to conform to normal responsiveness.